Effectiveness Of Trihalomethane (Thm) Precursors Removal In Groundwater Using Coagulant-Disinfectant - Ab Kadir, Nur Nadia (2017)
Trihalomethanes (THMs) is one of disinfection by-products (DBPs) groups and it will form due to the reaction between disinfectant and NOM in treated drinking water. Thus, as THM precursors, NOM needs to be removed through water treatment process. Therefore, this study applied commercialized coagulant-disinfectant powder, and carried out jar test applying two ferric-based coagulants, simultaneously with disinfectant, both to determine the effectiveness of THM precursors removal from groundwater. The coagulants applied in this study were, ferric sulphate and ferric chloride. Selected water quality parameter such as turbidity, DOC, UV254 and SUVA were tested for all water samples. For the first part, groundwater was treated by using commercialize coagulant-disinfectant powder. By using this commercialized powder, about 28.36% - 48.68% of turbidity has been removed while for UV254, range of the percentage removal obtained was between 12.12% - 34.11% which was less than turbidity removal. Besides, it was found that, DOC had a very poor removal, only 2.14% - 12.94%. By using this commercialized powder, chloroform and bromodichloromethane were found to exceed the limit specified by Ministry of Health, greater than 0.200 mg/L and 0.060 mg/L, respectively. On the other hand, the use of ferric-based coagulant provided a higher percentage removal for all parameters compared to commercialize coagulant-disinfectant. Ferric sulphate showed to have a good turbidity removal, the highest at 50.51% while ferric chloride is great in UV254 removal, as the percentage removal obtained reached until 80.76%. From the various conditions of pH and coagulants dose tested, at pH 5.5, THMs formed less for both coagulants compared to other pH levels, though all those values still exceeded the limit. Previous study found that, there will be adverse health effects to human which includes potential to get cancer disease due to long term use/consumption of water with elevated THM level.